Urgent need for better quality control, standards and regulation for the Large Language Models used in healthcare domain - Sathian, Brijesh; van Teijlingen, Edwin; do Nascimento, Israel Junior Borges; Kabir, Russel; Banerjee, Indrajit; Simkhada, Padam; Al Hamad, Hanadi (Nepal Journal of Epidemiology, 2024)
Current methodologies for ensuring AI technology safety and efficacy may be adequate for earlier AI iterations predating generative artificial intelligence (GAI). However, governing clinical GAI may necessitate the development of novel regulatory frameworks. As AI technology advances, researchers, academic institutions, funding bodies, and publishers should continue to examine its impact on scientific inquiry and revise their understanding, ethical guidelines, and regulations accordingly.